Fractal Analysis and Hurst Parameter for Intrapartum Fetal Heart Rate Variability Analysis: A Versatile Alternative to Frequency Bands and LF/HF Ratio - Doret, Muriel; Spilka, Jiří; Chudáček, Václav; Gonçalves, Paulo; Abry, Patrice (PLoS One, 2015)
BACKGROUND: The fetal heart rate (FHR) is commonly monitored during labor to detect early fetal acidosis. FHR variability is traditionally investigated using Fourier transform, often with adult predefined frequency band powers and the corresponding LF/HF ratio. However, fetal conditions differ from adults and modify spectrum repartition along frequencies. AIMS: This study questions the arbitrariness definition and relevance of the frequency band splitting procedure, and thus of the calculation of the underlying LF/HF ratio, as efficient tools for characterizing intrapartum FHR variability. STUDY DESIGN: The last 30 minutes before delivery of the intrapartum FHR were analyzed. SUBJECTS: Case-control study. A total of 45 singletons divided into two groups based on umbilical cord arterial pH: the Index group with pH ≤ 7.05 (n = 15) and Control group with pH > 7.05 (n = 30). OUTCOME MEASURES: Frequency band-based LF/HF ratio and Hurst parameter. RESULTS: This study shows that the intrapartum FHR is characterized by fractal temporal dynamics and promotes the Hurst parameter as a potential marker of fetal acidosis. This parameter preserves the intuition of a power frequency balance, while avoiding the frequency band splitting procedure and thus the arbitrary choice of a frequency separating bands. The study also shows that extending the frequency range covered by the adult-based bands to higher and lower frequencies permits the Hurst parameter to achieve better performance for identifying fetal acidosis. CONCLUSIONS: The Hurst parameter provides a robust and versatile tool for quantifying FHR variability, yields better acidosis detection performance compared to the LF/HF ratio, and avoids arbitrariness in spectral band splitting and definitions.
Keywords: Fractals; porodní děj; těhotenství; studie případů a kontrol; Humans; Fetal Monitoring; asfyxie novorozenců; monitorování plodu; fraktály; Asphyxia Neonatorum; srdeční frekvence plodu; Labor, Obstetric; Heart Rate, Fetal; Infant, Newborn; acidóza; novorozenec; ženské pohlaví; lidé; Case-Control Studies; Pregnancy; Acidosis; Fetal Blood; fetální krev; Female